The Investigation of Sexual and Species Dimorphism in the Foot of Chukar Partridge (Alectoris chukar) and Gray Partridge (Perdix perdix) Using Geometric Morphometric and Symmetric Analyses - Mustafa Sedat Arslan; Hacer Baş Ekici (Veterinary Sciences and Practices)
Morphological differences can provide insights into species' ecological adaptations and evolutionary processes. This study focuses on examining the effects of sex and species dimorphism on foot morphology in two different partridge species, the Chukar Partridge (Alectoris chukar) and the Gray Partridge (Perdix perdix). A total of 68-foot samples, including both right and left foot, were analyzed from 34 partridges collected in Sivas province. The analysis revealed that, regardless of sex, the first toe of Chukar Partridges was longer than that of Gray Partridges. When comparing species, the angle between the toes of female Chukar Partridges was wider than that of female Gray Partridges, while the angle between the toes of male Gray Partridges was wider than that of male Chukar Partridges. In terms of sex differences, the angle between the toes of male Gray Partridges was wider than that of female Gray Partridges, while the angle between the toes of female Chukar Partridges was wider than that of male Chukar Partridges. The contribution of directional asymmetry to variation was found to be lower than that of fluctuating asymmetry in both shape and size, suggesting that the asymmetry may result from developmental differences rather than lateral bias. Overall, the width of the toe angle was linked to habitat preferences and ecological adaptations. These findings suggest that the foot morphology of partridges may be shaped by factors such as sex, species, and habitat, and that these adaptations may help birds cope with environmental challenges.